Penerapan Metode Gallery Walk untuk Meningkatkan Keterampilan Literasi Siswa di Sanggar Belajar Kepong Kuala Lumpur Malaysia - Putri Mei Lani Ayu Lestari; Ismail Saleh Nasution; Ikhwan Fauzi Nasution (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to improve students' literacy skills through the application of the Gallery Walk method at Sanggar Belajar Kepong, Kuala Lumpur, Malaysia. The study used a classroom action approach implemented in two cycles, with stages of planning, implementation, observation, and reflection. The research instrument was in the form of observation and assessment of literacy skills covering five indicators: understanding text, analyzing text, critical thinking, interpreting information, and writing and re-presenting information. The results showed a significant increase in students' literacy skills, from varying completeness in cycle I (the lowest indicator was 30%) to 100% completeness in four indicators and 80% in one indicator in cycle II. Learning with the Gallery Walk method has been proven to encourage activeness, critical thinking, and the ability to convey information effectively. These findings strengthen the results of previous studies which state that Gallery Walk is effective in improving students' literacy skills. In conclusion, the Gallery Walk method can be used as an alternative to innovative and enjoyable learning to improve student literacy.